2. How is the economic assessment of vaccines performed today?. Issue 1 (1st January 2017) - Standaert, Baudouin; Rappuoli, Rino
ABSTRACT: This paper describes how the economic assessment of vaccines is performed today. It discusses why it may be incomplete and explores potential approaches to adjust the analysis to be more comprehensive. Besides helping protect against serious disease, vaccines also help avoid mild disease episodes that may not receive medical attention but which have important societal consequences. They also benefit unvaccinated individuals by reducing disease transmission. Wider societal benefits may extend beyond a decrease in disease incidence, as lower transmission rates reduce the risk of epidemics, which in turn reduces the pressure on healthcare providers, and may improve the quality of care for patients with unrelated diseases. Vaccines also lower the use of antibiotics leading to less pressure on anti-microbial resistance. Conventional ICUA focuses on individual health benefits, like increased survival. Therefore, this approach may not adequately capture the wider vaccination benefits. We discuss differences between treatment and vaccine prevention in the economic assessment, and how ICUA has been adapted to cope with the inconsistencies. Although such adaptations may fulfil the demand of one specific stakeholder, they may not meet the needs of other stakeholders who operate at the societal level, such as ministries other than healthcare, employers, caregivers, and insurers.